Antibacterial Activity of Hibiscus sabdariffa (Rosella) Using Methanolic Extract - Venkatesan Keerthika; Venkatesan Santhosh; Manivannan N (Wolters Kluwer Medknow Publications, 2024)
Hibiscus sabdariffa L. (Rosella) has a long history of use in food preparation, herbal remedies, hot and cold beverages, food industry flavoring, and herbal drinks. More than 300 species of Hibiscus are grown all over the world. It is an annual herbaceous shrub belonging to the family Malvacea. However, limited is known about the antimicrobial properties of H. sabdariffa; the purpose of this study was to investigate the antimicrobial activity of H. sabdariffa (Rosella) extract against a range of pathogens, including Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans. The results of the study showed that H. sabdariffa (Rosella) extract had a significant antimicrobial effect, against S. aureus and E. coli. Further the minimum inhibitory concentration (MIC) shows 128 μg/mL concentration followed by E. coli 256 μg/mL. The biocompatibility of crude metabolites shows highly compatible with Red blood cells (RBC's). This finding suggests that the crude metabolites of H. sabdariffa (Rosella) could be the source to control the human pathogens.